Caraterização fenotípica e genotípica de comunidades bacterianas da água do Rio Cuiabá - Sarto, Karina Augusta (2013)
The Cuiabá River has great importance in Mato Grosso, because more than a third of the population is located in its catchment area, where 46% of the funding sources of water for domestic consumption of various municipalities in the basin come from this river. As the population growth, occurred in the region of Cuiabá a deterioration of water quality of Cuiabá and Coxipó rivers (Coxipó tributary of the Cuiabá), since the streams are also used as a place of dilution of domestic and industrial effluents. So is this working hypothesis that the deposit of waste in the Cuiabá River, besides influencing the fauna and flora, also interferes on microbiota. To test this hypothesis, this study aims to: isolate and quantify total cultivable aerobic heterotrophic microorganisms and nitrogen-fixing bacteria in water samples from eight (8) sampling points of the Cuiabá River, and genotypically characterized isolates through BOX PCR. Were conducted six (6) bimonthly collections within one (1) year. Samples were inoculated onto plates containing four (4) different cultures (TSA for heterotrophic total, NFb, Meio 79 and JMV for specific groups of nitrifying) and incubated at 35 o C for 144 hours, and performed readings every 24 hours to count the colony forming units (CFUs). You can see the difference in the amount of CFUs / mL between points, and P4 and P6 were those with greater abundance in the order of 5,5 x 105 mL-1 and 1,1 x106mL-1 , respectively, and in cultivation in TSA P2 and P3 the less abundant in the order of 9,1 x103 mL -1 and 3,6 x103mL-1 , respectively, for the same culture medium. The nitrifying showed similar behavior, with some exceptions in places that are not very abundant heterotrophic total, but have lots of specific groups of bacteria. It is also noticeable the difference between seasonal periods, so that the first samples collected at the beginning of the rainy season had higher abundance than the latest collections featuring the dry period. Four hundred sixty six (466) microbial strains of the four culture media were isolated. In the Gram analysis was found that 8.16% of the identified bacteria are Gram-Positive cocci; 9.01% are Gram-Negatives cocci, 36.48% are Gram-Positive rods, and 46.35% are Gram- Negative rods. DNA was extracted from 135 isolates that were later subjected to DNA amplification by PCR. In genotypic analysis of BOX-PCR, we can see that there is a greater similarity between the strains isolated from the same culture media, and a greater diversity of genetic profiles in the initial stretch of the river (P1, P2 and P3), since the intermediate section which characterizes the urban perimeter, there was xiv little variability, and in that final stretch was analyzed further as there is great diversity in the beginning, despite the quality of the water has already established.